Some New Ideas on the Role of Legal Analysis applied to the Regulation of Telecommunications Services in Brazil - Castro, Marcus Faro de; Fontes, Daniele Kleiner (Law, State and Telecommunications Review, 2016)
Purpose ”“ The paper aims to present new ideas and analytical approaches developed in recent years by Brazilian legal scholars regarding regulation and economic development. Regulatory law of telecommunications services is taken as an example of application of such new ideas and analytical approaches. Methodology/approach/design ”“ Two main approaches to the relationship between law and economic issues are described: the New Law and Development (NLD) approach and the Legal Analysis of Economic Policy (LAEP) perspective. The paper highlights prominent ideas of each perspective. Findings ”“ The paper shows that there are structured ideas available in recent Brazilian legal literature which have a non-negligible potential of being explored in legal discussions and analyses of economic policy and regulatory issues of many sectors of emerging economies, including the telecommunications industry. Originality/value ”“ The paper offers valuable contributions that may help in efforts to enhance and innovate the role of legal expertise in the regulatory process of several economic sectors, including the telecommunications sector.